2016
DOI: 10.1016/j.fsi.2016.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Langerhans-like cells in the immunocompetent tissues of channel catfish, Ictalurus punctatus

Abstract: Dendritic cells (DCs) are the most powerful antigen presenting cells (APCs) that have a critical role in bridging innate and adaptive immune responses in vertebrates. Dendritic cells have been characterized morphologically and functionally in the teleost fish models such as rainbow trout, salmonids, medaka, and zebrafish. The presence of DCs with remarkable similarities to human Langerhans cells (LCs) has been described in the spleen and anterior kidney of salmonids and rainbow trout. However, there is no evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…Our comparative genomics approach showed that the splicing event that generates Cbfβ2 likely emerged as early as in bony fish (M. Tenno and I. Taniuchi, unpublished data), despite Runx3 being already present in lamprey ( Nah et al, 2014 ). A recent study showed that LC-like cells are present in catfish ( Kordon et al, 2016 ), prompting us to speculate on an evolutionarily conserved role for Cbfβ2 in LC differentiation. Interestingly, the interaction between Runx2 and VDR was proposed to be involved in shaping the genetic program of osteoblastogenesis ( Marcellini et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our comparative genomics approach showed that the splicing event that generates Cbfβ2 likely emerged as early as in bony fish (M. Tenno and I. Taniuchi, unpublished data), despite Runx3 being already present in lamprey ( Nah et al, 2014 ). A recent study showed that LC-like cells are present in catfish ( Kordon et al, 2016 ), prompting us to speculate on an evolutionarily conserved role for Cbfβ2 in LC differentiation. Interestingly, the interaction between Runx2 and VDR was proposed to be involved in shaping the genetic program of osteoblastogenesis ( Marcellini et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the numbers of L/CD207 + cells during E. ictaluri infection, immunohistochemical staining of catfish AK, spleen, and gill tissue was performed with polyclonal antibodies (pAbs) specific to human CD207 (R&D Systems, Inc.) as described previously (40). Briefly, for antigen retrieval, tissue sections were incubated in target retrieval solution (DAKO) for 40 min at 100°C.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the same research group has observed DC-like cells containing Birbeck -like granules in the gills of Chinook salmon during Loma salmonae infection (39). Recently, our group identified L/CD207 + cells in the channel catfish AK, spleen, and gills by immunohistochemistry (IHC), and described cells that resembled mammalian LC DCs containing Birbeck-like granules in the spleen, anterior and posterior kidneys, and gills of channel catfish by transmission electron microscopy (40).…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest the possibility to characterize with Langerin/CD207, Langerhans-like cells in primitive vertebrates. Kordon et al (2016) carried out research on LCs in Ictalurus punctatus , channel catfish. Using antibodies to CD207, LCs-like cells have been labeled in the spleen and cephalic kidney of the catfish ( Fig.…”
Section: Langerin/cd207mentioning
confidence: 99%
“…Keratinocytes, through the release of cytokines, can modulate the functionality of LCs, modifying the type of induced response such as TNF alpha which is a powerful activator ( Groves et al, 1995 ). Several studies report the presence of cells morphologically and functionally similar to the LCs of mammals, also in the other vertebrate classes ( Kordon et al, 2016 ; Lauriano et al, 2014 , 2018 , 2019 , 2020 ; Lovy et al, 2006 , 2009 ; Zaghloul et al, 2017 ). These cells do not present only long dendrites but are characterized from cytoplasmic granules similar to the Birbeck ones and have been highlighted with LCs typical markers, such as CD207 and S-100, and for this reason they are called Langerhans–like cells.…”
Section: Introductionmentioning
confidence: 99%